Legal Politics of Qanun Aceh Number 11 of 2018 concerning Sharia Financial Institutions in the Field of Sharia Banking - Ichwan Ahnaz Alamudi; Muhammad Torieq Abdillah; Dian May Syifa; Muhammad Wahdini (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
This research is motivated by the gap between the ideals of the comprehensive implementation of the sharia-based financial system in Aceh and the reality of implementation which still faces various challenges, both in terms of regulation, institutions, and community readiness. Qanun Aceh Number 11 of 2018 concerning Sharia Financial Institutions (LKS) is the main instrument in realizing this transformation, so it is important to study it from the perspective of legal politics background that is the background of its formation. The purpose of this research is to analyze the legal politics in Qanun LKS and its implications for the Islamic banking sector in Aceh. This research uses a type of normative legal research with a qualitative approach, through a statute approach and a conceptual approach. The legal materials used consist of primary, secondary, and tertiary legal materials collected through literature studies, then analyzed descriptively-analytically. The results of the study show that Qanun LKS is a political and legal product that reflects the integration between Aceh’s special autonomy authority and the application of Islamic sharia in the economic sector, especially banking. The implementation of Qanun LKS encourages the conversion of the conventional banking system to sharia as a whole, but still faces various obstacles such as institutional readiness, infrastructure, and the level of public literacy. This study concludes that the success of these policies is highly dependent on the consistency of implementation, adaptive regulatory support, and increased public understanding of the Islamic financial system. The contribution of this research is to provide a comprehensive understanding of legal politics in Islamic financial regulation and become an evaluation material for the development of more effective policies in the future.